Examining green three-echelon supply chain structures link with product track scheme: Implications for green technologies - Wang, Min (Frontiers in Environmental Science, 2022)
The study aims to inquire the relationship between green three-echelon supply chain system and product line design with the emergence of green technologies. The study used a unique social welfare vector is presented for use in gauging the sustainability of product line design, and a sustainable product line design technique is provided for upstream suppliers to adjust the product categories they offer. This social welfare vector is a representation of a supply chain with one supplier, many producers, and one retailer. The provider may determine whether a product line design is Pareto optimum with the use of the social welfare vector and a multi-criteria model built on the principles of data envelopment analysis (DEA). The study findings came up with an alternate solution approach for upstream suppliers to achieve Pareto optimum product line design in huge data set scenario. This study also recommended multiple implications for manufacturers and retailers farther down the supply chain, who may use this information to increase the channel's sustainability through green energy technologies in product line systems.